Is Money Exogenous in Money-Demand Equations - Mehra, Y. P. (Journal of Political Economy, 1978)
Sims's finding that nominal money stock is strictly exogenous in a distributed-lag regression of nominal income on nominal money stock is not inconsistent with the appearance and real income and nominal interest rates as strictly exogenous regressors in the quarterly money-demand equations estimated in real form. This strict exogeneity of real income and interest rates in real money-demand equations is due to the restriction implied by estimation in the real form, and these implicit restrictions seem to conflict with the sample information.